Indonesian Society Perception in Intervention of Solar Panel Incentives - Nurmasitya Kemalaintan; Zulfahmi Noor; Muhammad Noor Arridho (Green Publisher Indonesia, 2026)
The use of residential solar panels is gradually being intensified by the government. Policies to support residential solar panel adoption are also being developed. In relation to policy implementation in Indonesia, field conditions need to be properly understood to ensure effective policy performance. This study, *Indonesian Society Perception in Intervention of Solar Panel Incentives*, examines the views of Indonesian society regarding solar panel incentives and their role in the decision to adopt solar panels. The aim is to identify incentives that are most suitable for implementation in Indonesia. Incentives identified based on the literature review include Feed-in Tariff, Net Metering, R&D Investment, Green Certification, and Education & Awareness Programs. This study uses the SODA (Strategic Options Development and Analysis) approach. Data collection was conducted through structured interviews. Interviews were carried out with households using solar panels as their main source of electricity to meet energy needs in the Yogyakarta area, as well as potential adopters who are part of an energy community. This community expressed both positive and negative perceptions of each incentive. The results indicate a positive perception of Feed-in Tariff, Net Metering, and Education & Awareness Programs, as these three incentives are considered more feasible and applicable within the current Indonesian context. Meanwhile, R&D Investment and Green Certification are perceived negatively, as they are considered costly and less directly beneficial for immediate adoption. Based on these findings, the most suitable incentive for Indonesian society is the Education & Awareness Program.